2010
DOI: 10.1136/thx.2009.125930
|View full text |Cite
|
Sign up to set email alerts
|

Double-stranded RNA induces disproportionate expression of thymic stromal lymphopoietin versus interferon-  in bronchial epithelial cells from donors with asthma

Abstract: Background Thymic stromal lymphopoietin (TSLP) is an epithelial cell-derived cytokine that strongly activates dendritic cells and can initiate allergic inflammation. Since exposure to rhinovirus or double-stranded (ds) RNA (a surrogate of viral infection) induces TSLP expression in bronchial epithelial cells (BECs), this cytokine may link innate antiviral responses and the type 2 adaptive immune response. Objective As BECs from donors with asthma have a deficient interferon (IFN) response to rhinovirus infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

20
148
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(170 citation statements)
references
References 36 publications
20
148
0
Order By: Relevance
“…2012b; Uller et al. 2010) and COPD tissues (Mallia et al. 2010), and IFN‐ β has been recently trialed in a Phase I/II study for efficacy on naturally occurring asthma exacerbations (Djukanovic et al.…”
Section: Discussionmentioning
confidence: 99%
“…2012b; Uller et al. 2010) and COPD tissues (Mallia et al. 2010), and IFN‐ β has been recently trialed in a Phase I/II study for efficacy on naturally occurring asthma exacerbations (Djukanovic et al.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies with PBECs from non-asthmatic and asthmatic individuals have highlighted differences in the cellular response after exposure to environmental agents with the potential to cause epithelial damage. For example, it has been shown that monolayer cultures of PBECs derived from moderate-to-severe asthmatic individuals have a deficient innate immune response to rhinovirus infection by producing less interferon (IFN)-β (Wark et al, 2005), and this is paralleled by higher levels of the Th2-promoting chemokine, thymic stromal lymphopoietin (TSLP) (Uller et al, 2010). Based on the observation that exogenous IFN-β restores the anti-viral response and suppresses viral replication (Cakebread et al, 2011), clinical trials using inhaled IFN-β as a new treatment for virus-induced exacerbations have reported a beneficial effect in a subgroup of patients with severe asthma (Djukanović et al, 2014).…”
Section: Cfdeo-/6rep-cftrmentioning
confidence: 99%
“…TSLP is a cytokine secreted by the airway epithelium in response to respiratory viruses and is known to promote allergic Th2 responses in asthma. Bronchial epithelium from asthmatic adults produces more TSLP compared with healthy controls when stimulated by double-stranded RNA [68]. However, there is no data in children except for a clinical study that showed increased TSLP in nasal secretions during rhinovirus-induced asthma exacerbations [69].…”
Section: Innate Immune Responsesmentioning
confidence: 91%